Hypoxia and expression of the proapoptotic regulator BNIP3 in cervical cancer. Issue 3 (1st April 2006) - Leo, C.; Horn, L. C.; HÖCKEL, M.
Abstract : Hypoxia plays a major role in the malignant progression of tumors. Here, we investigate the expression of Bcl-2/adenovirus E1B 19 kd-interacting protein 3 (BNIP3), a proapoptotic Bcl-2 family member, and its relationship to hypoxia in cervical cancer cell lines and clinical samples of cervical cancer. Cervical cancer cell lines were grown under hypoxia or normoxia, and BNIP3 mRNA expression was examined by Northern blot analysis. In 50 patients with cervical cancer, intratumoral oxygen measurement with the Eppendorf electrode and needle biopsies of the tumor were performed. The obtained tissue was subsequently analyzed by immunohistochemistry with an anti-BNIP3 antibody. Cervical cancer tissue collected upon surgery was used for Northern blot analysis of in vivo BNIP3 mRNA expression. BNIP3 mRNA is strongly induced under hypoxic conditions in all cervical cancer cell lines investigated. Furthermore, Northern blot analysis revealed that BNIP3 mRNA is expressed in cervical cancer tissue. Using immunohistochemistry, we demonstrated that BNIP3 protein is expressed in 82% of the investigated cervical cancers and that more advanced tumor stages showed significantly stronger BNIP3 expression. However, we observed no correlation between BNIP3 expression and intratumoral hypoxia. In conclusion, BNIP3 is expressed in different cervical cancer cell lines as well as in clinical samples of cervical cancer. Although BNIP3 is clearly hypoxia-inducible in vitro, our results suggest additional mechanisms of BNIP3 regulation in vivo. Our findings therefore highlight a discrepancy between in vitro models of tumor hypoxia and the complexity of human cancer.